A Self-Adhesive Ginsenoside Rk3/Metformin-Loaded Hydrogel Microneedle for Management of Systemic Sclerosis - Yuanyuan Wang; Caiyun Zhong; Kexin Wang; Shihong Shen; Daidi Fan (Gels)
Microcirculation damage, dermal thickening, and difficulty in the spatiotemporal coordination of key platelet factor 4 (CXCL4) and transforming growth factor-β (TGF-β) contribute to the lack of effective treatments for systemic sclerosis (scleroderma, SSc). To address these challenges, we proposed a novel synergistic drug combination of ginsenoside Rk3 (CXCL4 regulator) and metformin (Met, TGF-β regulator) based on molecular docking and developed an ultra-long release, dual-target regulation hydrogel microneedle system (Rk3/Met URS MN). The rapidly dissolving tips of this hydrogel microneedle consisted of polyvinyl alcohol and polyvinylpyrrolidone, and were loaded with polydopamine-coated, coordination-induced self-assembled Rk3/Met nanomedicines. These micro-tips could spatiotemporally synchronize transdermal delivery of the hydrophobic Rk3 and hydrophilic Met, providing ultra-long release for up to 10 days with a single administration. The recombinant collagen CF-1552/oxidized pullulan-based (CAOP) hydrogel backing exhibited skin self-adhesiveness and excellent mechanical properties and could perform localized moisture retention and free radical scavenging at the lesion site. In vitro and in vivo efficacy studies, along with bioinformatics analysis of RNA sequencing, demonstrated that the Rk3/Met URS MN achieved immune modulation, anti-inflammatory effects, angiogenesis promotion, and antifibrosis in SSc through synergistic CXCL4/TGF-β dual-target regulation. Notably, on the 10th day, the dermal thickness decreased from 248.97 ± 21.3 μm to 152.7 ± 18.1 μm, with no significant difference from the normal group, indicating its significant potential in clinical applications in SSc.